Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/maco.201005735
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of deterioration in reinforced concrete structures by AE technique

Abstract: Acoustic emission (AE) technique is gaining increasing interest for applications in civil engineering. AE indeed is a passive nonintrusive technique that can be applicable either in structural health monitoring (global evaluation) and in defect localization (local evaluation). The most promising application of such a technique seems to be however in the evaluation of growing defects. Defects such as cracks and delamination can be caused by reinforcement corrosion as well as by other concrete deterioration mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 19 publications
(21 reference statements)
2
14
0
Order By: Relevance
“…Referring to these figures, there is a rapid increase in the slope of the CSS curve within intervals of 1000 -2000s and at the final stage of the testing within 2500 -3000s. These outcomes are almost similar to the previous research work by [17]. Throughout the time of interval, the values of HI are highly peak correspond to the slope increase of the CSS curve value.…”
Section: A Signal Strength Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…Referring to these figures, there is a rapid increase in the slope of the CSS curve within intervals of 1000 -2000s and at the final stage of the testing within 2500 -3000s. These outcomes are almost similar to the previous research work by [17]. Throughout the time of interval, the values of HI are highly peak correspond to the slope increase of the CSS curve value.…”
Section: A Signal Strength Analysissupporting
confidence: 81%
“…These ranges of values are similar with the previous research and this signifies the release of the high energy content in the beam specimens, where as the damages are continuously being more serious till to failure stage such as breakage of the concrete structure and shear failure [17].…”
Section: A Signal Strength Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…e accumulated internal energy releases suddenly in the form of elastic waves, thus resulting in the AE phenomenon. Scholars have made abundant researches on rock AE characteristics during the deformation and failure process [4][5][6][7]. Lavrov [8] observed the Kaiser effect in a brittle limestone cyclically loaded with different loading rates and found that damage formed in rock at a high loading rate can hardly be revealed by reloading with slow rate, yet the damage formed during loading with slow rate can be successfully revealed by using fast reloading.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of reinforced concrete are usually exposed to a wide variety of damaging influences that leads to reduction in the strength, utility and aesthetic quality of structures [1,2]. Aside from mechanical stress, corrosion due to chemical and environmental attacks is one of the most damaging processes in concrete [3][4][5] causing great concern for civil and structural engineers.…”
Section: Introductionmentioning
confidence: 99%